2021
DOI: 10.36076/ppj.2021/24/235
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Anesthetic Quality Between Interscalene Block and Superior Trunk Block for Arthroscopic Shoulder Surgery: A Randomized Controlled Trial

Abstract: Background: Interscalene block is the most commonly used nerve block for shoulder surgery, and superior trunk block has been investigated as a phrenic-sparing alternative. This randomized controlled trial compared ultrasound-guided interscalene block and superior trunk block as anesthesia for arthroscopic shoulder surgery. Objectives: Our aims were to determine the superiority of anesthesia quality and compare the risk of hemidiaphragmatic paralysis between these 2 blocks. Study Design: A randomized, controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Previously, 3 studies of superior trunk block, in which 2 used 15 mL of 0.5% ropivacaine and 1 used 20 mL of mixture of 2% lidocaine and 0.75% ropivacaine, reported incidences of complete hemidiaphragmatic paralysis of 5.3% (2 of 38), 4.8% (3 of 62), and 12.5% (3 of 24), respectively. 19,21,25 We initially speculated that the subparaneural upper trunk block would further decrease the incidence of complete hemidiaphragmatic paralysis due to the use of a lower injection volume and a more distal block along the brachial plexus. However, our final incidence was 6.3% (3 of 48).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, 3 studies of superior trunk block, in which 2 used 15 mL of 0.5% ropivacaine and 1 used 20 mL of mixture of 2% lidocaine and 0.75% ropivacaine, reported incidences of complete hemidiaphragmatic paralysis of 5.3% (2 of 38), 4.8% (3 of 62), and 12.5% (3 of 24), respectively. 19,21,25 We initially speculated that the subparaneural upper trunk block would further decrease the incidence of complete hemidiaphragmatic paralysis due to the use of a lower injection volume and a more distal block along the brachial plexus. However, our final incidence was 6.3% (3 of 48).…”
Section: Discussionmentioning
confidence: 99%
“…A larger trial using a 2-point posterior/anterior injection technique demonstrated HDP rates of just 4.8% for STB with 15 mL of LA, significantly less than the ISB [ 49 ]. However, a study using a similar injection technique [ 50 ] showed no significant difference between HDP incidence in ISB and STB groups. A subsequent study injecting 12 mL of bupivacaine deep (posterior) into the superior trunk also produced high incidences of HDP [ 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…All but one RCT comparing STB to ISB found that STB provided noninferior analgesia and similar 24-hour opioid consumption levels. Only the study by Lee et al [ 50 ] analysed anaesthetic effect of STB rather than purely its postoperative analgesic effect (i.e., its ability to be used without the use of GA) and found that STB produced a lower anaesthesia grade than ISB.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The superior trunk, a short distance distal from the interscalene location, may be less likely to cause pulmonary compromise. However, an RCT comparing superior trunk block to ISB for shoulder arthroscopy (both combined with intravenous sedation) showed that superior trunk blockade did not reduce the rates of hemidiaphragm paralysis and provided lower quality of surgical anesthesia [28 ▪▪ ]. The authors point out that many factors influence outcomes after nerve blocks, suggesting that the excellent results reported with superior trunk blockade do not always translate well to other practices.…”
Section: Choice Of Nerve Blockmentioning
confidence: 99%